Are dietary patterns differently associated with differentiated levels of mental health problems? Results from a large cross-sectional study among Iranian manufacturing employees. Issue 1 (7th January 2019) - Heidari, Zahra; Feizi, Awat; Roohafza, Hamidreza; Rabiei, Katayoun; Sarrafzadegan, Nizal
Abstract : Objectives: The present study aimed to classify participants based on mental health problems profile and to evaluate its relationship with dietary patterns among Iranian manufacturing employees. Design: Observational study with a cross-sectional design. Setting: This study was conducted in Esfahan Steel Company, one of the biggest Iranian industrial manufacturing companies. Participants: Complete data on 2942 manufacturing employees, with a mean (SD) age of 36.68 (7.31) years, were analysed. Outcome measures: Hospital Anxiety and Depression Scale(HADA) and General Health Questionnaire (GHQ-12) were used to evaluate anxiety and depression and psychological distress, respectively. Results: Three major dietary patterns, namely 'western', 'healthy' and 'traditional', were extracted using factor analysis. A two-class, one-factor structure was identified from study participants in terms of mental health problems profile based on the factor mixture model. Two identified classes were labelled as 'low mental health problems' (2683 manufacturing employees, 91.2%) and 'high mental health problems' (259 individuals, 8.8%). After adjusting for the impact of potential confounders, manufacturing employees in the highest tertile of healthy dietary pattern had lower odds of being in the high mental health problems profile class (OR=0.67, 95% CI 0.49 to 0.92). In contrast, greater adherence to Western and traditional dietary patterns was associated with increased odds of being in the high mental health problems class (OR=1.66, 95% CI: 1.18 to 2.35 and OR=1.52, 95% CI :1.10 to 2.11, respectively). Conclusions: Our study provided informative pathways on the association of dietary patterns and mental health among manufacturing employees. The findings can be used by workplace health promotion policymakers in improving mental health in such study population. Interventional and prospective studies that investigate the effects of change in dietary patterns on the mental health of manufacturing employees are suggested.